Enhanced electro-photo synergistic catalysis of Pt (Pd)/ZnO/graphene composite for methanol oxidation under visible light irradiation. (10th January 2016) - Li, Zhongshui; Ye, Lingting; Lei, Fengling; Wang, Yanli; Xu, Shuhong; Lin, Shen
Graphical abstract: Highlights: Pt (Pd)/ZnO/GNs composite was synthesized via one-pot hydrothermal process. Highly dispersed Pt (Pd) nanoparticles are assembled onto Pt (Pd)/ZnO/GNs composite. Pt (Pd)/ZnO/GNs serves as an efficient electro-photo synergistic catalyst for MOR. Electro-photo synergistic catalysis is realized under UV/visible light irradiation. ZnO bandgap narrowing favors better synergistic effect in visible light irradiation. Abstract: One-pot method is used to synthesize Pt (Pd)/ZnO/graphene composite (simplified as Pt (Pd)/ZnO/GNs). Under hydrothermal conditions, weak basic Zn 2+ ions (pH = 9.0) is converted to ZnO, accompanying synchronous reduction of K2 PtCl4 (K2 PdCl4 ) and graphene oxide (GO) without additional reducing agent. ZnO deposited on the surface of graphene nanosheets (GNs) offers homogeneous nuclei to anchor metal particles, leading to the uniform dispersion of Pt (Pd) particles, with average diameter of 3.0 nm for Pt and 5.5 nm for Pd. Electrochemical experiments show that Pt/ZnO/GNs and Pd/ZnO/GNs have much higher catalytic activity and stability for methanol oxidation reaction (MOR) and improved tolerance of CO compared with commercially available Johnson Matthey 20% Pt/C catalyst (Pt/C-JM) and Sigma-Aldrich 20% Pd/C catalyst (Pd/C-SA). Under light irradiation, catalytic activities of Pt (Pd)/ZnO/GNs are drastically enhanced, with the mass activities of 1724.2 mA mg −1 (UV irradiation) & 1935.5 mA mg −1 (visible irradiation) for Pt/ZnO/GNs, and 733.5 mA mg −1 (UV irradiation) & 818.3 mA mg −1 (visible irradiation) for Pd/ZnO/GNs. The improved performance mainly derives from the synergistic effects between the electro-catalysis of well dispersed Pt (Pd) nanoparticles and photo-catalysis of ZnO. And the band gap narrowing of ZnO in Pt (Pd)/ZnO/GNs contributes to the enhanced synergistic catalysis effects under visible light irradiation, which provides new opportunities for exploiting efficient visible light assisted electro-catalytic methanol oxidation reaction.